Colloidal Osmotic and Metabolically Active Substances in Therapy for Lung Lesions in Acute Severe Intoxications With Neutropic Poisons - G. A. Livanov; A. N. Lodyagin; I. P. Nikolayeva; B. V. Batotsyrenov (Общая реаниматология)
Monitoring of the blood circulation and liquid sectors in patients with lung lesion due to severe acute intoxications makes it possible to perform infusion therapy that does not induce thoracic hyperhydration. The inclusion of gelofusin and cytoflavin into the infusion regimen by the proposed procedure substantially enhances the efficiency of treatment of patients with this pathology even when acute lung lesion syndrome develops.